Application of CRISPR/Cas-based gene-editing for developing better banana - Tripathi, Leena; Ntui, Valentine O.; Tripathi, Jaindra N. (Frontiers in Bioengineering and Biotechnology, 2024)
Banana (Musa spp.), including plantain, is one of the major staple food and cash crops grown in over 140 countries in the subtropics and tropics, with around 153 million tons annual global production, feeding about 400 million people. Despite its widespread cultivation and adaptability to diverse environments, banana production faces significant challenges from pathogens and pests that often coexist within agricultural landscapes. Recent advancements in CRISPR/Cas-based gene editing offer transformative solutions to enhance banana resilience and productivity. Researchers at IITA, Kenya, have successfully employed gene editing to confer resistance to diseases such as banana Xanthomonas wilt (BXW) by targeting susceptibility genes and banana streak virus (BSV) by disrupting viral sequences. Other breakthroughs include the development of semi-dwarf plants, and increased β-carotene content. Additionally, non-browning banana have been developed to reduce food waste, with regulatory approval in the Philippines. The future prospects of gene editing in banana looks promising with CRISPR-based gene activation (CRISPRa) and inhibition (CRISPRi) techniques offering potential for improved disease resistance. The Cas-CLOVER system provides a precise alternative to CRISPR/Cas9, demonstrating success in generating gene-edited banana mutants. Integration of precision genetics with traditional breeding, and adopting transgene-free editing strategies, will be pivotal in harnessing the full potential of gene-edited banana. The future of crop gene editing holds exciting prospects for producing banana that thrives across diverse agroecological zones and offers superior nutritional value, ultimately benefiting farmers and consumers. This article highlights the pivotal role of CRISPR/Cas technology in advancing banana resilience, yield and nutritional quality, with significant implications for global food security.